Bacitracin is a non-competitive inhibitor of porcine M1 family neutral and glutamyl aminopeptidases. Issue 17 (19th August 2021) - Arrebola, Yarini; Rivera, Laura; Pedroso, Alejandro; McGuire, Rory; Tresanco, Mario E. Valdes; Bergado, Gretchen; Charli, Jean-Louis; Sánchez, Belinda; Pascual Alonso, Isel
Abstract: Membrane alanyl and glutamyl aminopeptidases (APN and APA, respectively) are established targets for the development of biomedical tools in human pathologies. APN overexpression correlates with the progression of tumours, including melanoma. Bacitracin, widely used as a topical antibiotic, inhibits subtilisin-like serine peptidases and disulphide isomerases. In the present contribution, we demonstrate that bacitracin is a non-competitive α = 1 and α < 1 inhibitor of porcine kidney APN and APA, respectively, with Ki values in the micromolar range. To test a potential application of this result, we assayed the effect of bacitracin on murine melanoma MB16F10 cell line viability. We demonstrated the cell line expresses an APN-like activity inhibited by bacitracin and bestatin. Additionally, we identified a cytotoxic effect of bacitracin. Further experiments are required to understand in depth the mechanisms of action of bacitracin on melanoma cells. They will clarify the therapeutic potential of bacitracin for melanoma treatment. Graphical Abstract: UF0001